Pharmaceuticals in Water: Risks to Aquatic Life and Remediation Strategies - Aqib Hassan Ali Khan; Rocío Barros (Hydrobiology, 2023)
The presence of pharmaceuticals in the aquatic environment presents a challenge to modern science. The most significant impact this can induce is the emergence of antibiotic resistance, which can lead to a global health emergency. It is important to note that the impact of pharmaceuticals in the aquatic environment is not limited to antibiotic resistance. Pharmaceuticals can also affect the behaviour and reproductive systems of aquatic organisms, with cascading effects on entire ecosystems. Numerous studies have reported the emergence of pharmaceuticals due to the uncontrolled disposal of polluted domestic, agricultural, and industrial wastewater in water bodies. This work discusses the potential of pharmaceuticals that on one hand are highly important for mankind, yet their non-judicious usage and disposal induce equally intriguing and problematic conditions to the health of aquatic systems. Pathways through which pharmaceutics can make their way into water bodies are discussed. Furthermore, the risk imposed by pharmaceuticals on aquatic life is also elaborated. The possible and pragmatic remediation methods through which pharmaceutical products can be treated are also discussed. Emphasis is placed on the potential of phytoremediation and advanced oxidative process, and the factors affecting the efficacy of these remediation methods are discussed.